URBAN WATERSHED CONSERVATION UNDER MULTI-ACTOR GOVERNANCE: EVIDENCE FROM ZAMBOANGA CITY, PHILIPPINES (Lex localis - Journal of Local Self-Government, 2024)
Urban watersheds that supply drinking water to secondary cities often sit at the intersection of protected-area regulation, local land-use politics, and customary institutions. This article examines governance dynamics shaping watershed protection and conservation in Pasonanca Natural Park (PaNP), Zamboanga City, Philippines—an urban-source watershed that supports municipal water security and biodiversity conservation. Using a qualitative–quantitative case study design, the study integrates (a) institutional and policy analysis of multi-level mandates under the National Integrated Protected Areas System and local government authorities, (b) land-cover assessment using government land-cover products and related protected-area reporting, and (c) documentary review of water-dependency and management constraints. Anchored in scholarship on polycentric and collaborative environmental governance, the analysis assesses how authority, coordination, financing, and legitimacy influence implementation outcomes (Dietz et al., 2003; Emerson et al., 2012; Ostrom, 2010). Findings indicate that PaNP’s statutory protection under national protected-area law is associated with sustained forest dominance, yet governance performance is constrained by institutional fragmentation across agencies and jurisdictions, limited enforcement capacity relative to watershed scale, and weak alignment between principal water beneficiaries and conservation financing. Land-use pressures concentrate along buffer-zone interfaces, where regulatory instruments are less integrated with protected-area management. Indigenous Subanen governance contributes conservation-consistent norms, but participation remains largely consultative rather than decisional, affecting legitimacy and compliance incentives (Dawson et al., 2021; Garnett et al., 2018). The article argues that urban watershed sustainability requires institutional reforms that (1) strengthen cross-boundary coordination and adaptive review cycles, (2) establish stable financing linked to ecosystem service beneficiaries, and (3) formalize co-management arrangements that recognize indigenous authority. These reforms can improve watershed resilience, reduce service vulnerabilities, and align urban water security with equitable conservation outcomes.